The Role of Quality Human Resources in Realizing Smart Cities - Rio Haribowo; Sugeng Karyadi; Sri Sudiarti; Roy Setiawan; Hartanto Hartanto (LPPPIPublishing, 2025)
Humans spend most of their time producing goods and services, which can come from factories or offices. They also spend some of their time consuming goods and services provided by others, other factories, or other offices. With the remaining time, humans also worry about what they will produce and consume in the future. Several activities take place within a city, where the approach considers the city as a living unit with integrated economic activities within it. Quality human resources are the main foundation in realizing a smart city because they are users, developers, and drivers of technology. The purpose of this study is to explain the role of quality human resources in realizing smart cities. To answer this question, a qualitative analysis approach was used, utilizing secondary data such as theoretical concepts from books and other relevant sources. The results show that quality human resources are skilled and digitally literate individuals who play a role in realizing smart cities by providing innovation in urban solutions, increasing the efficiency of public services, actively participating in decision-making, and contributing to the city's sustainable development.